THE MAGISTRACY AND JUDICIAL INDEPENDENCE: A STATE OF MIND OR THE STATE OF CIRCUMSTANCES? (The Pretoria Student Law Review, 2021)
Is judicial independence merely a state of mind or is institutional independence essential for judicial independence? This question is especially relevant with regard to the South African magistracy. Before 1994 the magistracy functioned in a system where no institutional independence existed. It was only with the advent of the interim Constitution in 1994 that institutional independence and the protection thereof began to apply to the magistracy. The question arises whether the Constitution freed the minds of the magistracy as if by magic, and whether institutional independence necessarily brings with it an independent state of mind.
Keywords: judicial independence; institutional independence; South African magistracy